Criminal legal nature of the premises of permitting a minor convicted in a special educational (medical and educational) institution: Belarusian-Russian model experience - Nagornov, Kirill I.; Shidlovsky, Andrey V. (Journal of the Belarusian State University. Law, 2020)
The authors study the legal regulation of one of the most severe measures of criminal legal influence in the current Belarusian and Russian legislation, which can be applied to minors convicted – placement in a special educational institution of a closed type, a special educational (medical and educational) institution. Based on the national legislative experience, the author reveals the features of the legal nature, essence and content of this measure, as well as identifies common features and problems in its legal regulation, with the justification of the most acceptable options for legislative consolidation of the studied measure of criminal legal impact on minors.
Keywords: compulsory measures of educational influence (nature); placement in a special educational (medical and educational) institution; a special educational institution of a closed type; a special educational institution of an open type